2018
DOI: 10.1002/anie.201807402
|View full text |Cite
|
Sign up to set email alerts
|

Lowering Molecular Symmetry To Improve the Morphological Properties of the Hole‐Transport Layer for Stable Perovskite Solar Cells

Abstract: Inspired by the structural feature of the classical hole-transport material (HTM), Spiro-OMeTAD, many analogues based on a highly symmetrical spiro-core were reported for perovskite solar cells (PSCs). However, these HTMs were prone to crystallize because of the high molecular symmetry, forming non-uniform films, unfavorable for the device stability and large-area processing. By lowering the symmetry of spiro-core, we report herein a novel spirobisindane-based HTM, Spiro-I, which could form amorphous films wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 40 publications
1
78
0
Order By: Relevance
“…As for FBA3, the improved lm morphology may be attributed to the fact that in comparison with FBA2, the molecular symmetry can be further destroyed due to meta-methoxy substitutions on the TPA units. 59 To test the effectiveness of these prepared uoranthene derivatives as dopant-free HTMs, a typical n-i-p planar PVSC was fabricated in a device conguration of ITO/C 60 /perovskite/ HTL/MoO 3 /Ag. The device fabrication details are described in the ESI.…”
Section: Resultsmentioning
confidence: 99%
“…As for FBA3, the improved lm morphology may be attributed to the fact that in comparison with FBA2, the molecular symmetry can be further destroyed due to meta-methoxy substitutions on the TPA units. 59 To test the effectiveness of these prepared uoranthene derivatives as dopant-free HTMs, a typical n-i-p planar PVSC was fabricated in a device conguration of ITO/C 60 /perovskite/ HTL/MoO 3 /Ag. The device fabrication details are described in the ESI.…”
Section: Resultsmentioning
confidence: 99%
“…Both SM‐HTMs show a weak π–π stacking peak either along the out‐of‐plane direction or in‐plane direction, indicating nearly amorphous nature of the MPA‐BTI and MPA‐BTTI pristine films. Nevertheless, it was found that superior film uniformity and morphological stability could be even more important than hole mobility in determining device performance of PVSCs . Based on space charge‐limited current (SCLC) method, the hole mobility of neat MPA‐BTI film is determined to be 3.99 × 10 −5 cm 2 V −1 s −1 which is comparable to that (2.13 × 10 −5 cm 2 V −1 s −1 ) of the widely used Spiro‐OMeTAD .…”
Section: Optical Electrochemical Thermal and Charge Transport Propmentioning
confidence: 92%
“…For deciphering this hidden factor, microscopic film morphology was investigated as it can play an important role in the overall performance of the photovoltaic application. [24a‐c] Figure shows the atomic force microscopy (AFM) topographies of HTM‐coated FTO glasses in this study. Figure a is the topographic image of spiro‐OMeTAD film; it appears homogeneous, except the observation of a few pits.…”
Section: Resultsmentioning
confidence: 99%